IMPLEMENTATION OF MASS COMPOSTING OF URBAN ORGANIC WASTE IN URBAN FARMING (KALIRUNGKUT VILLAGE, RUNGKUT DISTRICT, SURABAYA CITY): IMPLEMENTASI PENGOMPOSAN MASAL SAMPAH ORGANIK PERKOTAAN DALAM URBAN FARMING (KELURAHAN KALIRUNGKUT KECAMATAN RUNGKUT KOTA SURABAYA) - Bambang Gunawan; Husin Rayesh Mallaleng; Mahrus Ali; Sri Purwanti; Nurlina Nurlina; Fauziatun Nisak; Yeni Ika Pratiwi; Sri Hidayati (Yayasan Education and Social Center, 2022)
Garbage is a very large natural resource originating from housing and markets which ultimately waste becomes an important problem for densely populated urban areas if not utilized properly. Composting is basically an effort to activate microbial activities in order to accelerate the decomposition process of organic matter. The result of the reshuffle is called compost which is used as fertilizer that can provide nutrients for plants and improve soil fertility.)This activity is the implementation of appropriate technology in the mass composting of urban organic waste, especially in the empowerment of urban agricultural land (urban faming) which is carried out in the RW area. 02 Kalirungkut Village, Rungkut District, Surabaya City.The models offered to solve the problem of urban organic waste for partners are: 1). Help prepare assistance to improve expertise and skills in the management of urban organic waste mass composting; 2). Provide support in mobilizing community participation so that they consciously and voluntarily understand waste problems in order to become compost products that are beneficial for the cultivation of productive plants and greening the surrounding environment; The results of the implementation of this appropriate technology show that there is awareness of community participation in waste management by implementing the 3R (reduce, refuse, recycle) aimed at reducing the amount of waste starting at the source by sorting household waste in the form of organic waste and inorganic waste. With the urban agriculture movement, it can be an alternative to maintain family food security, besides being able to make a major contribution in providing green open space